2019
DOI: 10.1016/j.jad.2019.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking and other substance use disorders associated with recurrent suicide attempts in bipolar disorder

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…In the same cohort, increased frequency of tobacco product use and contemporaneous use of multiple tobacco products were associated with higher depressive symptoms 62 . Current cigarette smoking also predicted current and 9‐month suicidal ideation and behavior and was a leading predictor of repeated suicide attempts in bipolar disorder 63,64 …”
Section: Results: Epidemiology and Pharmacologymentioning
confidence: 99%
“…In the same cohort, increased frequency of tobacco product use and contemporaneous use of multiple tobacco products were associated with higher depressive symptoms 62 . Current cigarette smoking also predicted current and 9‐month suicidal ideation and behavior and was a leading predictor of repeated suicide attempts in bipolar disorder 63,64 …”
Section: Results: Epidemiology and Pharmacologymentioning
confidence: 99%
“…AUDIT scores were missing for 18 participants at baseline and 22 at follow-up, and these were coded as misuse if their average number of alcohol units consumed per week the previous 6 months exceeded 7 for females and 14 for males ( n = 2 at both baseline and follow-up), in line with recommendations for maximum alcohol consumption in the Nordic countries ( 18 ). Finally, current daily use of nicotine was recorded both at baseline and follow-up since nicotine use is strongly related to all other forms of substance use or misuse ( 19 ), and has also been found to be associated with psychiatric outcomes such as suicidal risk in BD ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic mechanisms related to suicide might differ depending upon specific phenotypes such as suicidal ideation (SI) or SA (Brent and Mann 2005 ; Mann et al 2005 ; Mullins et al 2014 ), and on underlying mental disorders. Also, multiple attempters showed demographic and clinical characteristics different from those of single attempters (Jeon et al 2010 ; Fedyszyn et al 2016 ; Arici et al 2018 ; Icick et al 2019 ; Papadopoulou et al 2020 ). In BD, previous studies reported multiple psychiatric comorbidities and substance abuse as clinical factors associated with repeated attempts (Arici et al 2018 ; Icick et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, multiple attempters showed demographic and clinical characteristics different from those of single attempters (Jeon et al 2010 ; Fedyszyn et al 2016 ; Arici et al 2018 ; Icick et al 2019 ; Papadopoulou et al 2020 ). In BD, previous studies reported multiple psychiatric comorbidities and substance abuse as clinical factors associated with repeated attempts (Arici et al 2018 ; Icick et al 2019 ). However, most genetic studies on SA have used a single phenotype defined as “at least one SA in a lifetime” (Mullins et al 2014 ; Mullins et al 2019 ; Erlangsen et al 2020 ; Ruderfer et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%